2017 International Conference on 3D Vision (3DV) 2017
DOI: 10.1109/3dv.2017.00011
|View full text |Cite
|
Sign up to set email alerts
|

DepthSynth: Real-Time Realistic Synthetic Data Generation from CAD Models for 2.5D Recognition

Abstract: Recent progress in computer vision has been dominated by deep neural networks trained over large amounts of labeled data. Collecting such datasets is however a tedious, often impossible task; hence a surge in approaches relying solely on synthetic data for their training. For depth images however, discrepancies with real scans still noticeably affect the end performance. We thus propose an end-to-end framework which simulates the whole mechanism of these devices, generating realistic depth data from 3D models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Specifically in [13], a 6D grasp pose detector has been trained in a simulator and transferred successfully to the real robot with 93% success rate without any special mechanisms used for transfer. In [24] it was shown that by enhancing simulated data to mimic the signal processing pipeline of a depth camera transfer can be further facilitated. We follow some of these ideas in this work.…”
Section: Related Workmentioning
confidence: 99%
“…Specifically in [13], a 6D grasp pose detector has been trained in a simulator and transferred successfully to the real robot with 93% success rate without any special mechanisms used for transfer. In [24] it was shown that by enhancing simulated data to mimic the signal processing pipeline of a depth camera transfer can be further facilitated. We follow some of these ideas in this work.…”
Section: Related Workmentioning
confidence: 99%
“…Planche et al in [24] generate synthetic depth data from 3D models. In this work, they try to understand the causes of the noise in the real depth data and mimic this noise in synthetic depth data.…”
Section: Related Workmentioning
confidence: 99%
“…Though synthetic data has been extensively used to train deep CNN models for real-world images [49,18,52,37], this approach has been relatively limited for medical imaging.…”
Section: Synthetic Endoscopy Data For Trainingmentioning
confidence: 99%